An autophagy program that promotes T cell egress from the lymph node controls responses to immune checkpoint blockade - Houbaert, Diede; Nikolakopoulos, Apostolos Panagiotis; Jacobs, Kathryn A.; Meçe, Odeta; Roels, Jana; Shankar, Gautam; Agrawal, Madhur; More, Sanket; Ganne, Maarten; Rillaerts, Kristine; Boon, Louis; Swoboda, Magdalena; et al. (Cell reports (Cambridge), 2024)
Lymphatic endothelial cells (LECs) of the lymph node (LN) parenchyma orchestrate leukocyte trafficking and peripheral T cell dynamics. T cell responses to immunotherapy largely rely on peripheral T cell recruitment in tumors. Yet, a systematic and molecular understanding of how LECs within the LNs control T cell dynamics under steady-state and tumor-bearing conditions is lacking. Intravital imaging combined with immune phenotyping shows that LEC-specific deletion of the essential autophagy gene Atg5 alters intranodal positioning of lymphocytes and accrues their persistence in the LNs by increasing the availability of the main egress signal sphingosine-1-phosphate. Single-cell RNA sequencing of tumor-draining LNs shows that loss of ATG5 remodels niche-specific LEC phenotypes involved in molecular pathways regulating lymphocyte trafficking and LEC-T cell interactions. Functionally, loss of LEC autophagy prevents recruitment of tumor-infiltrating T and natural killer cells and abrogates response to immunotherapy. Thus, an LEC-autophagy program boosts immune-checkpoint responses by guiding systemic T cell dynamics. [Display omitted] •Thwarting LEC autophagy prevents lymphocyte egress from the lymph node (LN)•LEC autophagy governs the S1P gradient and the intranodal dynamics of T and NK cells•Loss of LEC autophagy remodels niche-specific LEC phenotypes in tumor-draining LNs•LEC-autophagy blockade blunts efficacy of ICBs by sequestering T and NK cells in the LNs Houbaert et al. find that defective autophagy in lymphatic endothelial cells (LECs) prevents lymphocyte’s egress from lymph nodes. In tumor-bearing mice, LEC autophagy endorses the recruitment of peripheral T and NK cells to the tumor and ICB-driven antitumor immunity, further underscoring the lymph nodes as critical players in immunotherapy responses.